Private Tuition Industry in India Students’ Perspective - Prasad, Rajendra; Anshu Kumari (JOURNAL OF INDIAN EDUCATION, 2020)
Students in our country take private tuitions at a large scale that creates social, educational and financial problems for the middle and poor class students. This is an important but ignored section in educational research. This research paper seeks to find out the various forces which pull students to take private tuition outside the school. Students’ perspective was the central point of this research. Descriptive research method was adopted with quantitative approach to investigate the problem. A Five-point Likert Scale on student’s perspective towards private tuition was constructed and standardised. Findings revealed that the school teachers are themselves the key forces to press upon the students to take private tuitions. Factors like tutor’s reputation, friendliness and personal understanding, independency to choose skilled and effective tutor, tuition as guarantee of academic improvement, aspiration for high grades, lengthy syllabus and its non-completion and poor monitoring system in schools etc. attract the students to take private tuitions.